Cerebrospinal Fluid-Derived Microvesicles From Sleeping Sickness Patients Alter Protein Expression in Human Astrocytes - Dozio, Vito; Lejon, Veerle; Mumba Ngoyi, Dieudonné; Büscher, Philippe; Sanchez, Jean-Charles; Tiberti, Natalia (Frontiers in Cellular and Infection Microbiology, 2019)
Human African trypanosomiasis (HAT) caused by the extracellular protozoon Trypanosoma brucei, is a neglected tropical disease affecting the poorest communities in sub-Saharan Africa. HAT progresses from a hemolymphatic first stage (S1) to a meningo-encephalitic late stage (S2) when parasites reach the central nervous system, although the existence of an intermediate stage (Int.) has also been proposed. The pathophysiological mechanisms associated with the development of S2 encephalopathy are yet to be fully elucidated. Here we hypothesized that HAT progression towards S2 might be accompanied by an increased release of microvesicles (MVs), sub-micron elements (0.1-1µm) involved in inflammatory processes and in the determination of the outcome of infections. We studied the morphology of MVs isolated from HAT cerebrospinal fluid (CSF) by transmission electron microscopy and used flow cytometry to show that total-MVs and leukocyte derived-CD45+ MVs are significantly increased in concentration in S2 patients’ CSF compared to S1 and Int. samples (n=12 per group). To assess potential biological properties of these MVs, immortalized human astrocytes were exposed, in vitro, to MVs enriched from S1, Int. or S2 CSF. Data-independent acquisition mass spectrometry analyses showed that S2 MVs induced, compared to Int. or S1 MVs, a strong proteome modulation in astrocytes that resembled the one produced by IFN-γ, a key molecule in HAT pathogenesis. Our results indicate that HAT S2 CSF harbors MVs potentially involved in the mechanisms of pathology associated with HAT late stage. Such vesicles might thus represent a new player to consider in future functional studies.